2016
DOI: 10.1371/journal.pgen.1006183
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Mitochondria Mediator Gene TRIAP1 by miR-320b Loss Is Associated with Progression in Nasopharyngeal Carcinoma

Abstract: The therapeutic strategy for advanced nasopharyngeal carcinoma (NPC) is still challenging. It is an urgent need to uncover novel treatment targets for NPC. Therefore, understanding the mechanisms underlying NPC tumorigenesis and progression is essential for the development of new therapeutic strategies. Here, we showed that TP53-regulated inhibitor of apoptosis (TRIAP1) was aberrantly overexpressed and associated with poor survival in NPC patients. TRIAP1 overexpression promoted NPC cell proliferation and supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 51 publications
2
60
2
Order By: Relevance
“…A report describes that TRIAP1 is up-regulated in drug-resistant breast cancer cells and altered expression of TRIAP1 changes cellular sensitivity to doxorubicin in breast cancer [29]. MiR-320b-inhibited TRIAP1 is involved in progression in nasopharyngeal carcinoma [30]. Our data take a further step to the function of TRIAP1 in lung cancer.…”
Section: Mir-107 Negatively Correlates With Triap1 In Clinical Lung Cmentioning
confidence: 52%
“…A report describes that TRIAP1 is up-regulated in drug-resistant breast cancer cells and altered expression of TRIAP1 changes cellular sensitivity to doxorubicin in breast cancer [29]. MiR-320b-inhibited TRIAP1 is involved in progression in nasopharyngeal carcinoma [30]. Our data take a further step to the function of TRIAP1 in lung cancer.…”
Section: Mir-107 Negatively Correlates With Triap1 In Clinical Lung Cmentioning
confidence: 52%
“…unveiled that TRIAP1 (secreted by fibroblasts) was taken up by adjacent prostate cancer cells, PC3 and LNCaP, resulting in a pronounced cancer radioresistance . Studies have illustrated that TRIAP1 exerts antiapoptotic effects via its interaction with HSP70, which inhibits cytochrome c to activate the apoptotic protease activating factor 1 and in turn the downstream caspase‐9 . Moreover, we discovered that TRIAP1 is involved in the upregulation of several antioxidant proteins, which can help remove radiation‐induced ROS.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies demonstrated that both microRNA‐18a and microRNA‐320b target TRIAP1. Of note, abnormal downregulation of these microRNAs results in an elevated TRIAP1 expression, thus promoting the progression of ovarian cancer and nasopharyngeal carcinoma . The scientific consensus states that the cancer‐promoting role of TRIAP1 is probably associated with its inhibitory effect on apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations